ARCHITECTURAL SYMBOLISM AS INTERSEMIOTIC TRANSLATION:: MALCOLM BRADBURY’S THE HISTORY MAN - Nicolau, Felix (Belas Infiéis, 2014)
Campus novels describe isolated, almost autarchic utopias. In Malcolm Bradbury’s The History Man, this utopia is projected into a dystopian dimension by a functional and transparent architecture. The epoch is that of radical sociologists who fight against tradition, memory, privacy, and subtlety. The paper analyses the influence architecture can have on people’s minds and behaviours, or the damages inflicted by concrete-and-steel structures upon human configuration. This is a study about the excesses of structure.